1981
DOI: 10.1111/j.1474-919x.1981.tb04051.x
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Occurrence of Cooperative Polyandry

Abstract: Summary This paper discusses the relative position of cooperative polyandry among models for the evolution of both polyandry and cooperative breeding. Cooperative polyandry is described as the situation where more than one male and one female breed as a group with males sharing equally in copulations and the care of one set of young. Sequential and simultaneous polyandry are defined to show how they differ from cooperative polyandry. These systems generally are characterized by the care of only one parent for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Greater competition by males for females due to biased ASRs may also lead to changes in the mating system, primarily from monogamy to polyandry. Social polyandry is the rarest of avian mating systems and falls into two distinct categories depending on whether the females mate sequentially with single males who then care for the clutch alone (classical polyandry), or with multiple males who care for the clutch together (cooperative polyandry, Faaborg & Patterson, ; Oring, ). Whereas classical polyandry is a fixed mating system for a small proportion of bird species, cooperative polyandry appears to be more flexible within species, occurring when either females or the resources they need for nesting are scarce, which may then lead to males sharing females (Hartley & Davies, ).…”
Section: Introductionmentioning
confidence: 99%
“…Greater competition by males for females due to biased ASRs may also lead to changes in the mating system, primarily from monogamy to polyandry. Social polyandry is the rarest of avian mating systems and falls into two distinct categories depending on whether the females mate sequentially with single males who then care for the clutch alone (classical polyandry), or with multiple males who care for the clutch together (cooperative polyandry, Faaborg & Patterson, ; Oring, ). Whereas classical polyandry is a fixed mating system for a small proportion of bird species, cooperative polyandry appears to be more flexible within species, occurring when either females or the resources they need for nesting are scarce, which may then lead to males sharing females (Hartley & Davies, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cooperative polyandry is the case in which a female mates with multiple males who care for the clutch cooperatively (Faaborg and Patterson 1981). In parrots, to our knowledge, only Heinsohn et al (2007) and Ekstrom et al (2007) found genetic evidence for polyandry in Eclectus Parrots (Eclectus roratus) and Greater Vasa Parrots (Caracopsis vasa), respectively.…”
Section: Discussionmentioning
confidence: 95%
“…The social systems of the more than 200 cooperative-breeding bird species vary considerably but con- sist generally of a monogamous pair with related adult offspring that delay dispersal and help at the nest (see Brown 198 7). However, cooperative breeding may include not only nonbreeding helpers at the nest but also cooperative polygamy, where helpers participate in reproductive activities (Faaborg & Patterson 1981). Cooperative polygamy can be subdivided into polygyny-females sharing one male--or polyandry--males sharing one female (Brown 198 7, Davies 1991).…”
Section: Mating Systemmentioning
confidence: 99%
“…Cooperative polygamy can be subdivided into polygyny-females sharing one male--or polyandry--males sharing one female (Brown 198 7, Davies 1991). Polyandry can again be subdivided into sequential polyandry and cooperative polyandry, in which the female has persistent bonds with two or more males and copulates with these males and all males share in parental care (Faaborg & Patterson 1981). Cooperative polyandry is rare in birds and has been reported in fewer than 1 5 species (Faaborg 1986).…”
Section: Mating Systemmentioning
confidence: 99%